Tinjauan Hukum Islam Terhadap Peran Ganda Komunitas Perempuan Pencungkil Kelapa di Kelurahan Mendahara Ilir - Aris Aris; Nilfatri Nilfatri; Kurniawan Kurniawan; Haeran Haeran; Zeni Sunarti; Al Munip (Journal of Innovative and Creativity, 2025)
This study aims to examine the dual roles of women in the coconut-picking community in Mendahara Ilir Village, Mendahara District, and examine these roles from an Islamic legal perspective. These dual roles encompass domestic roles as wives and housewives, as well as public roles as breadwinners in the informal sector. This research employed a qualitative approach with fieldwork methods through observation, interviews, and documentation. The results indicate that women in this community contribute significantly to the family economy while still fulfilling their household responsibilities. From an Islamic legal perspective, this dual role is permissible as long as it does not neglect primary family obligations and does not conflict with Sharia principles. Islamic law values women's hard work and recognizes their right to work, provided they maintain good manners, family responsibilities, and Islamic values. Therefore, the dual role of female coconut-picking women in this region can be categorized as a form of social ijtihad that aligns with the maqasid of Sharia, particularly in the protection of life and property.